Tradición y originalidad en la obra de Eneas el táctico: la génesis de la historiografía militar - Vela Tejada, José (1993)
The study about the work of Aeneas the Tactician in relation to the historical context and literary witnesses allows to enclose it inside the evolution towards a writing culture which begins from the last years of the Vth century B. C. In spite of the ancient military historiography has not been shaped as a literary genre in his work, we may infer, at least, Aeneas was the pioneer of a writing tradition which acquired a definitive status in the limits of the historical and literary context.
Keywords: Eneas, -- el Táctico; Historiografía; Crítica literaria